The Pleural Effusion And Symptom Evaluation (PLEASE) study of breathlessness in patients with a symptomatic pleural effusion. Issue 5 (14th May 2020) - Muruganandan, Sanjeevan; Azzopardi, Maree; Thomas, Rajesh; Fitzgerald, Deirdre B.; Kuok, Yi Jin; Cheah, Hui Min; Read, Catherine A.; Budgeon, Charley A.; Eastwood, Peter R.; Jenkins, Susan; Singh, Bhajan; Murray, Kevin; et al.
Introduction: Pathophysiology changes associated with pleural effusion, its drainage and factors governing symptom response are poorly understood. Our objective was to determine: 1) the effect of pleural effusion (and its drainage) on cardiorespiratory, functional and diaphragmatic parameters; and 2) the proportion as well as characteristics of patients with breathlessness relief post-drainage. Methods: Prospectively enrolled patients with symptomatic pleural effusions were assessed at both pre-therapeutic drainage and at 24–36 h post-therapeutic drainage. Results: 145 participants completed pre-drainage and post-drainage tests; 93% had effusions ≥25% of hemithorax. The median volume drained was 1.68 L. Breathlessness scores improved post-drainage (mean visual analogue scale (VAS) score by 28.0±24 mm; dyspnoea-12 (D12) score by 10.5±8.8; resting Borg score before 6-min walk test (6-MWT) by 0.6±1.7; all p<0.0001). The 6-min walk distance (6-MWD) increased by 29.7±73.5 m, p<0.0001. Improvements in vital signs and spirometry were modest (forced expiratory volume in 1 s (FEV1 ) by 0.22 L, 95% CI 0.18–0.27; forced vital capacity (FVC) by 0.30 L, 95% CI 0.24–0.37). The ipsilateral hemi-diaphragm was flattened/everted in 50% of participants pre-drainage and 48% of participants exhibited paradoxical or no diaphragmatic movement. Post-drainage, hemi-diaphragm shape and movement were normal in 94% and 73% of participants, respectively. Drainage provided meaningful breathlessness relief (VAS score improved ≥14 mm) in 73% of participants irrespective of whether the lung expanded (mean difference 0.14, 95% CI 10.02–0.29; p=0.13). Multivariate analyses found that breathlessness relief was associated with significant breathlessness pre-drainage (odds ratio (OR) 5.83 per standard deviation (sd ) decrease), baseline abnormal/paralyzed/paradoxical diaphragm movement (OR 4.37), benign aetiology (OR 3.39), higher pleural pH (OR persd increase 1.92) and higher serum albumin level (OR persd increase 1.73). Conclusions: Breathlessness and exercise tolerance improved in most patients with only a small mean improvement in spirometry and no change in oxygenation. Breathlessness improvement was similar in participants with and without trapped lung. Abnormal hemi-diaphragm shape and movement were independently associated with relief of breathlessness post-drainage. The majority of patients improve after pleural fluid drainage. Abnormal diaphragmatic function may be an important contributor to breathlessness in patients with pleural effusion. http://bit.ly/2SyF8RW